Influence of pulse duration and water/air cooling ratio on the efficiency of Er:YAG 2940 nm laser in debonding of porcelain laminate veneers: An in vitro study. Issue 4 (29th April 2022) - AlBalkhi, Mohand; Hamadah, Omar
Abstract: Objective: To determine the effectiveness of different pulse durations (PD) and the water/air (W/A) cooling ratio of the Er:YAG 2940 nm laser that are required for debonding porcelain laminate veneers (PLV), by investigation of the needed time for PLV debonding (DT) and the changes in dental pulp temperature. Materials and Methods: Thirty‐six extracted noncarious human maxillary premolars were prepared for receiving PLV. Samples were randomly assigned to six different groups, based on PD and the W/A ratio: Groups A (50 µs, 1:1), B (50 µs, 3:3), C (100 µs, 1:1), D (100 µs, 3:3), E (300 µs, 1:1), and F (300 µs, 3:3). Veneers were debonded using laser irradiation by the same parameters (270 mJ, 15 Hz) with noncontact application mode. Results: All 36 veneers were debonded. Samples of the 50 and 100 µs PDs showed significantly shorter DT (7.4−17 s) than that of the 300 µs which showed significantly the longest DT (104 s) among all other groups ( p  < .001). However, the highest elevation of pulp temperature was observed in Group E (300 µs, 1:1) which reached (3.4°C). Conclusion: Using the 50 or 100 µs PD of the Er:YAG laser was more efficient than 300 µs in reducing DT of PLVs with minimal change in pulp temperature. W/A cooling ratio had minimal influence on the DT of PLV.